1986
DOI: 10.1002/bbpc.19860900814
|View full text |Cite
|
Sign up to set email alerts
|

Defects and Cation Diffusion in Magnetite (VII): Diffusion Controlled Formation of Magnetite During Reactions in the Iron‐Oxygen System

Abstract: Parabolic rate constants describing the kinetics of the exclusively diffusion controlled growth of magnetite scales during simple reactions in the iron‐oxygen system are derived on basis of preceding studies on the defect structure and on the transport properties of this oxide. Furthermore, experimental results for the formation of magnetite by solid state reaction between the iron oxides wüstite and hematite are reported and compared with calculated data.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
45
0

Year Published

1987
1987
2017
2017

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 54 publications
(47 citation statements)
references
References 8 publications
2
45
0
Order By: Relevance
“…Based on available space model, the oxidation kinetics of two ferritic-martensitic steels are developed to predict in supercritical water at 400 ∘ C, 500 ∘ C, and 600 ∘ C. The iron diffusion coefficients in magnetite and Fe-Cr spinel, which are extrapolated from studies of Backhaus-Ricoult and Dieckmann [17] and Töpfer et al [18], are used for calculation of oxidation kinetics of steels under supercritical water environment. The main conclusions are as follows.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Based on available space model, the oxidation kinetics of two ferritic-martensitic steels are developed to predict in supercritical water at 400 ∘ C, 500 ∘ C, and 600 ∘ C. The iron diffusion coefficients in magnetite and Fe-Cr spinel, which are extrapolated from studies of Backhaus-Ricoult and Dieckmann [17] and Töpfer et al [18], are used for calculation of oxidation kinetics of steels under supercritical water environment. The main conclusions are as follows.…”
Section: Resultsmentioning
confidence: 99%
“…The concentration of defects is linked to the oxygen activity in oxide scales and the diffusion coefficient of Fe ions is dependent on the oxygen activity in two oxide layers. The diffusion coefficient of Fe ions in magnetite can be expressed by oxygen activity and temperature, and the equation can be written [17]:…”
Section: H the Dissociation Of Oxide Scales Is Neglectedmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover it is consistent with the fact that the chemical reaction usually limits at lower temperatures. Backhaus-Ricoult and Dieckmann 33) also observed that phase interphase reaction can be the rate controlling step under these conditions.…”
Section: Limiting Stepmentioning
confidence: 83%
“…Formation of outer and inner oxide scales is governed by outward diffusion of Fe ions and by inward diffusion of O ions, respectively. The diffusivity of O ions in Fe 3 O 4 is reported to be much lower than that of Fe ions, 17) so that the thickness of the inner oxide scale may decrease as the thickness of the outer oxide scale increases at temperatures between 873 K and 973 K. However, the thickness of both the outer and inner oxide scales decreased at 1 073 K compared with the thicknesses at 973 K. This could be attributed to quick formation of a Cr-and Si-enriched layer, which would act as barrier for diffusion of Fe and O ions as described below.…”
Section: Steam Oxidation Testsmentioning
confidence: 99%